2011
DOI: 10.4103/0970-1591.82841
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for an early detection program for bladder cancer

Abstract: Introduction:A total of 356,557 new cases were diagnosed annually worldwide in 2009, it was estimated that 52,810 new patients were to be diagnosed with bladder cancer and there were 10,180 projected deaths from the disease in the USA. Despite being the fourth commonest cancer in men, we do not have an early detection/screening program for bladder cancer. The review was aimed at looking at the evidence for the rationale for an early detection program for bladder cancer.Materials and Methods:A detailed search o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
(59 reference statements)
0
11
0
1
Order By: Relevance
“…The other tumours are squamous cell carcinoma, adenocarcinoma, and rare varieties like small cell carcinoma. Clinical stage and grade are the two most important determinants of the prognosis of bladder cancer [ 7 ]. Previous studies show varying results in relation to sex ratio, proportion of muscle invasive disease, and histological types of bladder cancer in Sri Lanka and in neighbouring South Asian countries [ 2 , 8 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other tumours are squamous cell carcinoma, adenocarcinoma, and rare varieties like small cell carcinoma. Clinical stage and grade are the two most important determinants of the prognosis of bladder cancer [ 7 ]. Previous studies show varying results in relation to sex ratio, proportion of muscle invasive disease, and histological types of bladder cancer in Sri Lanka and in neighbouring South Asian countries [ 2 , 8 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examination of voided urine or bladder washing specimens for exfoliated cancer cells has high sensitivity in high-grade tumors but low sensitivity in low-grade tumors [2] . It has been shown that delays in the process of diagnosis leads to unsatisfactory outcomes and adverse effects for the patient involved [3,4] . Therefore, there is a real clinical need to develop and integrate a non-invasive, sensitive and specific technique to assist in bladder cancer diagnosis and differentiation between low-and high-grade diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic and bladder cancers count for (3–7% of all cancers), but pancreatic cancer (PC) is one of the deadest cancers, with a dismal 5-year survival rate of 6% [1]. The success of current cancer treatments depends strongly on the time of diagnosis, with early detection and identification of high risk patient populations resulting in the most favorable overall survivals in these diseases [1], [2]. It is expected that early detection and screening of high risk patient populations may have the most significant impact on altering overall survival in these diseases.…”
Section: Introductionmentioning
confidence: 99%